Labyrinth [compact disc, unabridged] - Coulter, Catherine (Coulter, Catherine. FBI thriller (Brilliance Audio (Firm))., 2019)
On a dark night, Agent Sherlock is driving along circuitous mountain roads in West Virginia when her car is suddenly T-boned at an intersection. As her car spins out of control, a man's body slams against her windshield. When she finally comes to, Sherlock has no memory of the accident, nor of the moments that led right up to it. But what she does know is that the man she hit is a local CIA analyst, and now he's missing.